PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS TERHADAP KEMAMPUANIKOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMPN 3 SUNGAI LIMAU - Nurfazira . (Departemen Matematika, 2022)
The imathematical communication skill is an important aspect and should be achieved in the learning of mathematicsi. The Importance of mathematical communicationi skilli for students make this capability ineed to be improved in thei learning process of imathematics. But iin reality at SMPN 3 Sungai Limau, this ability has not been fully mastred by students and it has not been faciltied by students to improve this ability properly. One effordi to overcome this problem is by applying cooperativei learningi Studenti Teams Achievementi Divisions modeli. The purpose of this study was to describe the ieffect of the applicationi of the STADi learning imodel on the development mathematical communication abilities of eighti grade students ofi SMPNi 3 Sungai Limau. This type of reseacrh isi ai pre-experimentali research design with Onei Shot Case Study iDesign. The isubject of thisi researchi is class VIII 1 SMPN 3 Sungai Limau. This research data was collected throught iquiz and test of imathematical communicationi abilities basede on the percentage of the number of student the average value, and the percentage of students mathematical communication abities has increased. This shows thati there is ani impact of ithe application of the STADi learning model on student mathematical communication abilities. So, it conclude thati therei is an effect of the STADi learning model ion student mathematical communication abilities.Keywordsi – iMathematical iCommunication Skill, Cooperativei Learning Model, iStudent iTeams Achievementi Divisions, One Shot Case Study Design